(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2021)
Recent research shows that teachers who have a pro-inclusion mindset are more likely to alter their lessons and curriculum to meet their students’ individual needs. Educator training programs are accountable for ensuring that teachers are prepared to teach inclusively. According to the findings of the study, pre-service teachers from two universities were polled about their attitudes toward inclusion and their readiness to teach in inclusive classrooms. A self-prepared questionnaire was utilized to gather data on the study’s participants, who were all second-year preservice teachers in the teacher training program. Despite a positive attitude toward inclusion, the study found that student teachers lacked the skills and experience necessary to teach in an inclusive environment. Recommendations for improving teacher training programs were drawn from this study.